Taxonomic revision of the flathead fish genus Platycephalus Bloch, 1785 (Teleostei: Platycephalidae) from Australia, with description of a new species - Imamura, Hisashi (Zootaxa, 2015)
The taxonomy of the fish genus Platycephalus Bloch, 1785 from Australia is revised following examination of all extant primary types of Australian species, including those previously synonymized.  The following 16 Australian species, including a single new species, are recognized in this study: Platycephalus angustus Steindachner, 1866, Platycephalus aurimaculatus Knapp, 1987, Platycephalus bassensis Cuvier, 1829, Platycephalus caeruleopunctatus McCulloch, 1922, Platycephalus chauliodous Knapp, 1991, Platycephalus conatus Waite & McCulloch, 1915, Platycephalus endrachtensis Quoy & Gaimard, 1825, Platycephalus fuscus Cuvier, 1829, Platycephalus grandispinis Cuvier, 1829, Platycephalus laevigatus Cuvier, 1829, Platycephalus marmoratus Stead, 1908, Platycephalus orbitalis Imamura & Knapp, 2009, Platycephalus richardsoni Castelnau, 1872, Platycephalus speculator Klunzinger, 1872, Platycephalus westraliae (Whitley, 1938) and Platycephalus australis sp. nov. [formerly confused with Platycephalus indicus (Linnaeus, 1758)].  Previously suggested synonymies of several species are reevaluated and a key provided for all Australian species of Platycephalus.